1991
DOI: 10.1007/bf01055911
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metals on early life stages of the brine shrimp,Artemia: A developmental toxicity assay

Abstract: The need for simple, fast and inexpensive tests to study metal pollution in the marine environment has become more pressing as utilization of coastal waters increases. To address this concern, the influence of four metals, cupric sulfate, lead nitrate, zinc sulfate and nickel sulfate, on emergence and hatching of the brine shrimp, Artemia, has been assessed. Occurrence of these easily recognized developmental milestones provides a convenient method to assay metal effects on development. Copper and lead were ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…The method which was used in this study was adopted from sargelous [15] with minor modification. Artemia cysts were hatching at 15-35 ppm of salinity within 24-36 hrs [13]. Even though in this study the salinity seawater was 9 ppm, a significant decrease in hatching ability of cyst in a medium which contain teratogenic substances indicated that the substances may affect the development of Artemia cysts.…”
Section: Fig 1: Hatching Ability Of Cyst In Teratogenic Substancesmentioning
confidence: 84%
See 1 more Smart Citation
“…The method which was used in this study was adopted from sargelous [15] with minor modification. Artemia cysts were hatching at 15-35 ppm of salinity within 24-36 hrs [13]. Even though in this study the salinity seawater was 9 ppm, a significant decrease in hatching ability of cyst in a medium which contain teratogenic substances indicated that the substances may affect the development of Artemia cysts.…”
Section: Fig 1: Hatching Ability Of Cyst In Teratogenic Substancesmentioning
confidence: 84%
“…Developmental toxicology test using the BST has been conducted by number of researchers to test the effects of several substances in development stages with different parameters, such as: Butyrylcholinesterase in the early development of the brine shrimp larvae [11]; effects of copper, cadmium, and zinc on the hatching success of brine shrimp [12]; effects of cupric sulfate, lead nitrate, zinc sulfate and nickel sulfate on early life stages of the brine shrimp [13]; developmentrelated differentials in naupliiar vulnerability for cadmium sulfate, mercuric chloride, and sodium azide (NaN 3 ) [4].…”
Section: Discussionmentioning
confidence: 99%
“…Similar experiments carried out with metal salts ZnSO4, CuSO4, and NiSO4 (purity g99.0%, Sigma) covering the 10 -1 -10 -9 M range also demonstrated that toxic effects could be detected at low concentrations (see Figure 3b). Calculated EC50(1 h) values (e.g., 7.8 ( 1.9 µM for Zn 2+ ) and trends were in agreement with those of the standard reference method (25). Iron chelator deferoxamine mesylate (purity 95%, Sigma) and the hydroxyl radical scavenger dimethyl sulfoxide (DMSO; purity g99.0%, Fluka), both known for their ability to protect Artemia against menadione bisulfite toxicity (23), were also tested in the respirometric assays.…”
Section: Resultsmentioning
confidence: 98%
“…1990;Rosowski et al 1997). Mechanistically, however, the emergence of nauplii is less clear, although the process is inhibited by heavy metals (Rafiee et al 1986b;Go et al 1990;MacRae and Pandey, 1991;Pandey and MacRae, 1991), bicarbonate deficiency (Trotman el aZ. 1987;Trotman, 1991) and metabolic perturbation (Trotman et aZ.…”
Section: Molecular Aspects Of Early Artemia Developmentmentioning
confidence: 97%